ANALISIS KARAKTER DAN PERILAKU SOSIAL SISWA YANG TERBENTUK MELALUI PROGRAM LANGIT BIRU DI SMP NEGERI 3 TUBAN - Agus Fathoni Prasetyo; Nurlaili Dina Hafni (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2018)
This study aims to determine the implementation of the Langit biru program and its impact on the social behavior of students in SMP Negeri 3 Tuban. This type of research is qualitative research. The research data was collected with several techniques, such as observation, interview, and documentation. Triangulation technique is done by means of triangulation method and source that is by checking the information result of interview with documentation and observation and match from one informant with other informant. The results of the discussion on the implementation of the Langit Biru program and its impact on the students' social behavior that the blue sky program implementation consists of planning, Implementation and evaluation process of the program consisting of religious culture program (morning habituation) and SMS sambung rasa that are both interrelated. Impact Implementation of the Langit Biru program on social behavior of students of SMP Negeri 3 tuban known most of the students behave well or positively. After the existence of the Langit Biru program the presentation of violations of students also declined. Good social behavior of students is influenced by the environment that always supervise and work together both school environment and family or community environment.